Neighborhood Connectivity and Social Sustainability: A Study of Hyderabad’s Residential Areas - Hina Marvi; Reena Majid Memon; Rabia Soomro; Irfan Ahmed Memon; Aneel Kumar (World)
Rapid ribbon development in Qasimabad Taluka, Hyderabad, has resulted in fragmented neighborhoods due to unplanned urban expansion. This study evaluates the critical factors influencing social sustainability in residential communities, focusing on neighborhood connectivity, safety, and green spaces. Employing a quantitative approach, data were collected through quota sampling from 5–7% of government-approved housing schemes in Qasimabad. A Satisfaction Index was developed to assess residents’ perceptions of accessibility, safety, amenities, and community engagement and analyzed via SPSS-22. Key findings revealed severe dissatisfaction: only 19% of private vehicle users reported satisfaction, while over 60% rated pedestrian and cycling infrastructure as inadequate. Green spaces intended for communal use deteriorated, causing a 21.58% reduction in satisfaction. Despite moderate daytime safety ratings (+53.95%), the overall social sustainability index remained negative (−148.61%). This study underscores the urgency of integrated urban strategies—enhancing accessibility, revitalizing green spaces, improving safety measures, and fostering community engagement—to address fragmentation and achieve socially sustainable neighborhoods.